Evaluation of sowing date and insecticides for the management of viruses and insect vectors on Lentil (Lenes Culinaris Medikus) in North Shewa, Ethiopia - Fekadu Tewolde; Beyene Bitew; Berket Ali; Almnew Fantaye; Alme Belete; Yifru worku; Kalkidan Yalew; Talef Yeshitila; Safaa G. Kumari; Seid A. Kema (Andalasian International Journal of Entomology, 2026)
Ethiopia is the leading lentil producer in Africa, yet national productivity has been in steady decline, driven by the rapid emergence of viral diseases and severe infestations of the pea aphid (Acyrthosiphon pisum). A field experiment was conducted at Enewari North Shewa during the 2022 and 2023 main cropping seasons to identify the best options for managing emerging lentil viruses and vectors. The experiment was laid out in a Randomized complete block design with four replications. The lentil variety Derso was integrated with two insecticides (profenophos 50% EC and Dimethoate 40% EC), including an untreated check, and four sowing dates were used as treatments. Virus disease incidence and Pea aphid population were recorded, yield and yield-related parameters were collected, and data were analyzed using R software. The outcomes revealed that insecticides combined with sowing date significantly reduced aphid populations and reduced virus incidence in lentil. Minimum number of Pea aphid infestation and low virus incidence (11%) recorded when planting lentil in the first week of August and spraying Dimethoate 40 % EC two times at a 7-day interval. Whereas the maximum number of pea aphids (35) and high virus incidence (22%) were recorded on untreated checks, indicating that the level of disease controlled by controlling the vector pea aphid accounts for 50%. Again, the highest seed yield (3303 kg) was obtained by spraying Dimethoate and planting lentil in the first week of August, compared with the low yield from the untreated check (1993 kg). Hence, integrating sowing date with Dimethoate in the first week of August resulted in 69.8% yield increments over the untreated. In general, the results indicated that virus and aphid vector management can be achieved by applying Dimethoate and adjusting the sowing date for lentil crops.